Re: Gjesdal S, Mæland JG, Svedberg P, Hagberg J, Alexanderson K. Role of diagnoses and socioeconomic status in mortality among disability pensioners in Norway—a population-based cohort study. Scand J Work Environ Health. 2008;34(6):479–482. - Gjesdal, Sturla; Mæland, John Gunnar; Svedberg, Pia; Hagberg, Jan; Alexanderson, Kristina (Scandinavian Journal of Work, Environment & Health, 2009)
' ' OBJECTIVES ': 'Several studies have shown increased mortality among disability pensioners. This study attempted to determine the causes of such an increase. ' ' METHODS ': 'A population-based study was carried out with 148 942 persons followed between 1990 and 1996 in Norway. Of this total, 6285 women and 4113 men were on a disability pension at baseline. A Cox proportional hazards analysis was carried out separately for the women and men in which all-cause mortality was the outcome variable. Disability pension status, disability pension diagnosis, age, educational level, and mean annual income were entered as explanatory variables. ' ' RESULTS ': 'Persons on a disability pension had a strongly increased mortality rate. The age-adjusted hazard ratio was 3.0 [95% confidence interval (95% CI) 2.4–3.8] for the women and 3.4 (95% CI 2.8–4.1) for the men on a disability pension, when they were compared with those not on a disability pension. When adjusted for education and income levels, the hazard ratios (HR) decreased significantly for the men, to 2.0 (95% CI 1.8–2.4), but not so for women (HR 2.5, 95% CI 2.2–2.9). Except for the men with musculoskeletal diagnoses, all of the diagnostic groups had hazard ratios above unity also after the adjustments were made. ' ' CONCLUSIONS ': 'The study confirmed high early mortality among Norwegian disability pensioners in the period 1990–1996. The medical condition seemed to contribute more to the increased mortality among the women, whereas a low socioeconomic status was more important for the men.
Keywords: amendment and correction; cohort study; diagnosis; disability pensioner; medical condition; mortality; Norway; population-based cohort study; short communication; socioeconomic status